ANALYSIS OF INVENTORY CONTROL OF RAW MATERIALS FOR OYSTER MUSHROOMS PLANTING MEDIA IN UMKM AQSHA GUNUNG LINGKAS URBAN VILLAGE, EAST TARAKAN - Etty Wahyuni MS; Banyuriatiga Banyuriatiga; Saderiah Saderiah (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
UMKM Aqsha is a Small and Medium Enterprise that produces oyster mushrooms in Tarakan City. In the implementation process, the inventory for oyster mushrooms has yet to use the calculation method of EOQ analysis. In this case, there might be a media shortage of raw planting materials. The objectives of the research were to (1) describe the system of controlling the inventory for oyster mushrooms planting media raw materials based on actual conditions at UMKM Aqsha, (2) analyze the system of controlling the inventory for oyster mushrooms planting media raw materials using economic order quantity analysis, buying frequency, safety stock, reorder point and maximum inventory. The technique of taking informants was conducted by selecting the key informants, namely business owners and workers who know the information needed in the research. The analysis method used economic order quantity analysis, buying frequency, safety stock, reorder point and maximum inventory. The results of the research showed that the inventory control of UMKM Aqsha required all three raw materials totaling 3,345 kg in a year, with a one-time order quantity for the three raw materials totaling 1,115 kg. The inventory control implemented by UMKM Aqsha was not optimal yet and also has not yet implemented a reorder point. So that it was not possible to prevent a shortage of the three raw materials during the production process. EOQ analysis was given an optimum order for all three materials with 1,655.9 kg of raw materials, no safety stock for all three materials, a reorder point for all three materials with 526,17 kg of raw materials, and for the maximum inventory for all three materials with 1655.9 kg of raw materials.